Adi in the Shape Town Learning Application Using Gamification Features - Abd. Rouf, Nur Sabrina; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2022)
The conventional medium used in learning or teaching through book is less interactive. Thus, Adi in the Shape Town learning application is proposed to help children who aged six years old to learn about basic 2D shapes in more interactive way. The project aims to design the application by using educational gamification approach, to develop the application on Android platform, and to test the developed application to target users. The proposed application would have three game modules, and in each game module, there will be five levels provided. Also, Multimedia Mobile Content Development (MMCD) methodology is chosen as the methodology that helps in the whole process of finishing the project. The testing result has shown that 80% of the respondents have left positive feedbacks towards the proposed application. Thus, Adi in the Shape Town application will help users to learn basic 2D shapes through variety of game approaches.